Relevansi Sanksi Pidana dalam Penegakan Hukum Protokol Kesehatan pada Masa Pandemi Covid-19 - Ni Putu Ayu Mia Paramartha Sari; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2022)
There is a void in norms related to regulations governing violations of the COVID-19 health protocol as a crime, so it is appropriate to use criminal sanctions because this is an issue that must be clarified. The purposes of this study are to analyze legal arrangements for law enforcement of health protocols during the Covid-19 pandemic and regarding criminal sanctions in law enforcement of health protocols during the Covid-19 pandemic. This study uses normative legal research, using a statutory approach, a historical approach, and a conceptual approach. The sources of legal materials used by the author are primary and secondary legal materials using library techniques. The analysis technique was carried out qualitatively and presented in descriptive form. The findings reveal that the regulation of violations of the COVId-19 health protocol can be classified as an administrative crime based on administrative criminal law terminology, but in principle the legality of violating the COVID-19 health protocol does not have a clear legal basis because its enforcement is still using Article 212, 216, and 218 of the Criminal Code, Article 93 of the UU Law and Article 14 of the Infectious Disease Outbreak Law. In addition to this, the criminal sanctions contained in the legal rules which are considered to cover law enforcement for violations of the COVID-19 health protocol do not fully meet the elements of the ideal sentencing goal.